Nanoengineered Catalysts for Efficient Hydrogen Production in ‎Renewable Energy Systems - Awasthi , Kanchan; Mohapatra , Dr. Tapas Kumar; Prabu, Dr. D.; Kalidhas , Aravindan Munusamy; Saraswat, Vivek; Upadhyay , Dr. Satish; Dhingra, Lovish (International Journal of Basic and Applied Sciences, 2025)
Hydrogen (H2) is gaining acceptance as a renewable energy source (RES) that may replace or supplement the current carbon-based power ‎framework. Despite research in this domain frequently emphasizing the fundamental comprehension of catalytic mechanisms and ‎showcasing their efficacy across various approaches, considerable effort remains necessary to create superior methods and sophisticated ‎materials for extensive application. Nanoengineering methodologies at the nano or micron level are particularly compelling, as they facilitate ‎the exploration of how activity fluctuates based on variables such as dimension, substance, framework, electronic properties, and support ‎interactions. This understanding yields knowledge about structure–performance correlations in generating hydrogen, thereby optimizing ‎efficiency and permitting systematic development of a Nanoengineering catalyst (NC) with targeted functions and preference for hydrogen ‎generation. Traditional methods generate significant greenhouse gas (GHG) emissions owing to elevated manufacturing costs and restricted ‎effectiveness. Water separation (WS) presents one of the most environmentally sustainable production methods when integrated with RES. ‎Although expensive, it is afflicted by detrimental consequences that diminish efficiency. By elucidating physical properties and structural ‎relationships, NC approaches profoundly influence green H2 production. Additional research is necessary for storage facilities for H2 that ‎are robust for distant transportation networks with adequate refueling stations, while also improving the function of NC in RES-H2 generation frameworks‎.